Pendampingan Pembuatan Website Desa Sebagai Wujud Digitalisasi Administrasi dan Informasi Desa Plancungan, Slahung, Ponorogo, Jawa Timur - Sup, Devid Frastiawan Amir; Setiawan Bin Lahuri; Imam Kamaluddin; Khoirul Umam; Akhmad Affandi Mahfudz; Syamsuri; Achmad Michael Adi Putra; Nur Ihsan; Savier Nayaka Gunawardana; Abdullah Chamber; Muhammad Halimul Umam; Fatahna Fathan Mubina; Tegas Bijaksana; Ibnu Yaqzan Qurany; Muhammad Haidar; Lathiif Chandra Septian; Lucky Adha Febrian (LP3M IAIFA Kediri, 2025)
The development of the shoe industry offers great potential to support national economic growth in Indonesia, including in the Tambakrejo Village area, Sidoarjo, which is one of the largest producers of local shoe production in Indonesia. However, the development of shoe products in Tambakrejo Village is known to face many challenges. So, this research aims to find out what challenges are faced in developing local shoe industry MSMEs in Tambakrejo Village, Sidoarjo. Also, what are the results of the implementation of business management training and marketing strategies to develop local shoe industry MSMEs in Tambakrejo Village, Sidoarjo. This research uses the Participatory Action Research (PAR) method, which is carried out by combining active participation from the community or group that is the research subject in this research process. Data collection in this service is carried out in two ways, namely observation and interviews. The research results show that business management training and marketing strategies have a big impact in improving the quality of leather shoe products in Tambakrejo Village. The training provided helps craftsmen use digital marketing through e-commerce and social media to reach a wider market.